Computational Design and Bioinformatic Insights into Recombinant Whey Protein Production - Aathish Gurunathan; Harini Subalakshmi M (Nepal Journal of Biotechnology)
The rising global demand for sustainable protein sources highlights the need for alternatives to traditional whey protein production, which is resource-intensive and environmentally taxing. This study presents an in-silico approach for producing recombinant whey proteins—α-lactalbumin and β-lactoglobulin—using Saccharomyces cerevisiae as a host. Codon-optimized gene constructs were designed and validated through computational tools, showing enhanced translational efficiency, structural stability, and functional potential. Allergenicity analysis revealed moderate risk, suggesting a need for further refinement. Overall, the findings demonstrate the feasibility of precision fermentation for scalable, eco-friendly whey protein production, with broad applications in functional foods and biotechnology.